PENGELOLAAN SAMPAH DI BANJAR TEGEH SARI KELURAHAN TONJA DENPASAR UTARA - Yudistira Adnyana; Bagus Arya Wijaya; Made Mariada Rijasa (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The government of Denpasar City is currently carry out a source-based waste solution program. Banjar Tegeh Sari is one of the banjars in Tonja Village, East Denpasar, that has implemented a waste management program. The problems of partners from Banjar Tegeh Sari and Banjar Tegeh Sari Foundation: 1. The administrators (prajuru) of Banjar Tegeh Sari have yet a customary regulations (perarem) on waste management; 2. Residents haven’t get any information, seeding and maintenance skills as well as business opportunities for maggot cultivation. The implementation method is carried out by: phase of requirement planning, and phase of implementation. The solution to overcome the waste problem is by: making customary regulations (perarem) so that residents will comply and participate in waste management. The solution for maggot cultivation is carried out by providing training on maggot cultivation to a group of residents in Gang Sari Dewi. The implementation of the Perarem-making activities began with literature study, discussion, drafting, discussion and submission of Perarem draft on waste to be discussed and ratified in the Banjar Tegeh Sari forum (parum). The implementation of maggot cultivation activities began with library research, discussions, preparing equipment, socialization and training on maggot cultivation to the community group of Gang Sari Dewi, Banjar Tegeh Sari.